The journeys of a Taymiyyan Sufi - Post, Arjan. (Leiden ; Boston)
xvi, 321 sayfa
Keywords: “The Journeys of a Taymiyyan Sufi explores the life and teachings of 'Imād al-Dīn Aḥmad al-Wāsiṭī(d. 711/1311), a little-known Ḥanbalī Sufi master from the circle of Ibn Taymiyya (d. 728/1328). The first part of this book follows al-Wāsiṭī's physical journey in search of spiritual guidance through a critical study of his autobiographical writings. This provides unique insights into the Rifā'iyya, the Shādhiliyya, and the school of Ibn 'Arabī, several manifestations of Sufism that he encountered as he travelled from Wāsiṭ to Baghdad, Alexandria, and Cairo. Part I closes with his final destination, Damascus, where his membership of Ibn Taymiyya's circle and his role as a Sufi teacher is closely examined. The second part focuses on al-Wāsiṭī's spiritual journey through a study of his Sufi writings, which convey the distinct type of traditionalist Sufism that he taught in early eighth/fourteenth-century Damascus. Besides providing an overview of the spiritual path unto God from beginning to end as he formulated it, this reveals an exceptional interplay between Sufi theory and traditionalist theology.“ --